"Do This in Remembrance of Me": A Socio-Rhetorical Interpretation of the Lord's Supper in 1 Corinthians 11:23-29 - Donny Jhon Lionel Manurung (Global Education Journal, 2026)
The Lord's Supper is one of the most fundamental liturgical practices in the Christian tradition. Among the key texts that shape the church's understanding of this sacrament is 1 Corinthians 11:23-29, where the Apostle Paul transmits the tradition he "received" regarding the institution of the Lord's Supper, framed by the command: "Do this in remembrance of Me." This article argues that this command is not merely a memorial ritual but a theological and rhetorical act that forms the identity and communal life of the believing community. Using Vernon K. Robbins' socio-rhetorical interpretation, the study analyzes five textures of the text: inner texture (linguistic patterns, narrative structure, declarative-imperative dynamics), intertexture (connections to Jewish Passover tradition), social and cultural texture (interaction with Mediterranean banquet customs), ideological texture (construction of apostolic authority, deconstruction of honor-shame ideology, and reconstruction of community identity), and sacred texture (discourse on covenant, eschatological presence, and judgment). The findings demonstrate that Paul's corrective response to the Corinthian community, which had allowed social stratification to distort the meaning of the Supper, shows that the Eucharist cannot be separated from communal ethics and social justice. The command "Do this in remembrance of Me" is thus a call for the church to embody the meaning of the cross in solidarity, unity, and faithful witness. This study contributes to the discourse on biblical interpretation and liturgical theology, offering a reading that is contextual, ethically engaged, and relevant for contemporary church practice.